2020
DOI: 10.1080/00461520.2019.1691004
|View full text |Cite
|
Sign up to set email alerts
|

Semantic congruence in arithmetic: A new conceptual model for word problem solving

Abstract: Arithmetic problem solving is a crucial part of mathematics education. However, existing problem solving theories do not fully account for the semantic constraints partaking in the encoding and recoding of arithmetic word problems. In this respect, the limitations of the main existing models in the literature are discussed. We then introduce the Semantic Congruence (SECO) model, a theoretical model depicting how world and mathematical semantics interact in the encoding, recoding and solving of arithmetic word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 91 publications
3
34
1
2
Order By: Relevance
“…Thus, the schema theory and the Situation-Problem-Solver model both struggle to account for the results of our six experiments. On the other hand, those results are well within the scope of the new Semantic Congruence (SECO) model, which provides a conceptual framework for arithmetic word problem solving (Gros et al, 2020).…”
Section: Implications For Mathematical Word Problem Solvingsupporting
confidence: 58%
See 3 more Smart Citations
“…Thus, the schema theory and the Situation-Problem-Solver model both struggle to account for the results of our six experiments. On the other hand, those results are well within the scope of the new Semantic Congruence (SECO) model, which provides a conceptual framework for arithmetic word problem solving (Gros et al, 2020).…”
Section: Implications For Mathematical Word Problem Solvingsupporting
confidence: 58%
“…When no relevant solving algorithm can be specified from the interpreted structure, then solvers may attempt to engage in semantic recoding by using mathematical knowledge to construct a new representation of the problem at hand. When performed successfully, this semantic recoding makes it possible to use different solving algorithms compatible with the new constructed representation (Gros et al, 2020). Fig.…”
Section: Implications For Mathematical Word Problem Solvingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that general semantic knowledge about the entities featured in a problem interfere with its solving process, by means of an interpreted structure describing one's interpretation of the situation depicted in the problem (Bassok, 2001). More recently, the SECO framework (Gros, Thibaut, & Sander, 2020a), suggested that an initial semantic representation is encoded based on the problem statement and on the solver's general, non-mathematical knowledge about the entities it features. This approach notably predicts that an inappropriate encoding of a given problem statement may sometimes be semantically recoded into a new representation, in an attempt to overcome a dead end and find the solution to an arduous problem.…”
Section: Introductionmentioning
confidence: 99%